Enhancement of C-phycocyanin purity using negative chromatography with chitosan-modified nanofiber membrane - Ng, I-Son; Tang, Malcolm Siong Yii; Show, Pau Loke; Chiou, Zih Ming; Tsai, Jung Chin; Chang, Yu Kaung (Elsevier, 2019)
In this work, a chitosan-modified nanofiber membrane was fabricated and used to examine the permeation characteristics of C-phycocyanin (CPC) obtained from Spirulina platensis. The effects of NaCl concentration (0.1–1.0 M), chitosan coupling pH (6–8), chitosan coupling concentration (0.1–3.0%), algal solution pH (6–8), algal mass concentration (0.1–1.0% dw/v), and membrane flux (4.08 × 10 −2 –2.04 × 10 −1 mL/min·cm 2 ) on the penetration performance of the membrane for CPC were investigated. The results show that the order of binding selectivity of the membrane for these proteins is contaminating proteins (TP) > allophycocyanin (APC) > CPC. TP and APC molecules were more easily adsorbed by the chitosan-modified membrane, and the CPC molecules most easily penetrated the membrane without being adsorbed, enhancing CPC purity. The purification factor and total mass flux were 3.3 fold and 66%, respectively, in a single step. © 2019 Elsevier B.V.